The incorrect “Walra’s law” and a possible correction - García-Cobián Jáuregui, Ramón (1996)
The so-called Walras law tends to be presented as if to confirm the impossibility of imbalances in a single market. The author provides us with an example that shows us where the "law" is off the mark. The article then proposes a number of alternative versions that correct its errors, imposing sufficient conditions on relations of preference to demonstrate the validity of the correct form of the Walras law.